2007
DOI: 10.2337/db07-0425
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CC Chemokine Ligand 2 Does Not Limit Obesity-Associated Infiltration of Macrophages Into Adipose Tissue

Abstract: Macrophage recruitment to adipose tissue in obesity contributes to enhanced adipose tissue inflammatory activity and thus may underlie obesity-associated metabolic dysfunction. Obese adipose tissue exhibits increases in CC chemokine ligand 2 (CCL2, or monocyte chemoattractant protein-1), an important macrophage-recruiting factor. We therefore hypothesized that elevated CCL2 may contribute to obesity-associated adipose tissue macrophage recruitment. Male 6-week-old CCL2؊/؊ and wild-type mice (n ‫؍‬ 11-14 per gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(177 citation statements)
references
References 44 publications
11
159
3
4
Order By: Relevance
“…2, A and B, and supplemental Fig. 1), and this is consistent with previous studies (25). The increase in ATM content in the epididymal fat pad was comparable with accumulation of ATMs in other visceral depots such as mesenteric and retroperitoneal fat.…”
Section: Resultssupporting
confidence: 80%
“…2, A and B, and supplemental Fig. 1), and this is consistent with previous studies (25). The increase in ATM content in the epididymal fat pad was comparable with accumulation of ATMs in other visceral depots such as mesenteric and retroperitoneal fat.…”
Section: Resultssupporting
confidence: 80%
“…The lack of correlation between macrophage infiltration and expression of the inflammatory cytokines in gWAT at week 35 remains to be explained. However, it is compatible with other results showing that the absence of MCP-1 does not limit the recruitment of macrophages to gWAT, 52 and the lack of a correlation between macrophage content in gWAT and the levels of proinflammatory cytokines in plasma in mice fed HF diet. 19,28 In fact, the previous study 19 in mice fed HF diet for 12 weeks after weaning showed similar plasma levels of TNFa, interleukin-6, interleukin-1b, MCP-1 and granulocyte-macrophage colony-stimulating factor in male and female mice, in spite of a robust sexual dimorphism in macrophage infiltration and in the expression of genes for inflammatory markers in gWAT.…”
Section: Discussionsupporting
confidence: 81%
“…Coincidently, Inouye and co-workers showed that CCL2-deficient mice exhibited increased HFD-induced weight gain and comparable macrophage recruitment capabilities to control mice. CCL2-deficient mice also displayed impaired glucose tolerance, and in fact presented increased plasma glucose and reduced adiponectin levels compared with control mice (96) . These studies suggest that infiltrating macrophages are not solely pro-inflammatory and indicate that factors independent of CCR2/CCL2 are involved in macrophage recruitment.…”
Section: Obesity-induced Adipose Tissue Macrophage Recruitmentmentioning
confidence: 99%
“…Lack of CCR2 reduced HFDinduced obesity, while plasma CCL2 levels decreased exponentially with pharmacological-induced weight reduction in DIO mice (51,93) . A number of studies have disputed the involvement of the CCR2/MCP-1 axis in obesity and IR (93,96) . Abrogating CCR2 in DIO mice did not alter body weight, glucose homoeostasis or ATM infiltration (93) .…”
Section: Obesity-induced Adipose Tissue Macrophage Recruitmentmentioning
confidence: 99%